Q: 2XSquared - 3x-11 equals 0

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

33

x = -1.5 or -2 2x2 + 7x + 6 = 0 => (2x + 3)(x + 2) = 0 Thus 2x + 3 = 0 => x = -1.5 or x + 2 = 0 => x = -2

(x - 4)(2x + 3)

use algebra and then factor... x= -9 and 9

2x2 - 8x + 3 = 0 needs to be solved using the quadratic formula.x = (4 + sqrt(10))/2 or x = (4 - sqrt(10))/2

Related questions

It has roots x = 2.618 and x = 0.38197

(3,11)

(3,11) is a factor pair of 33.

33

2x2 - 9x = 18 2x2 - 9x -18 = 0 (2x - 18)(x + 9) x= -9 and 9

3x11 = 33

x = -1.5 or -2 2x2 + 7x + 6 = 0 => (2x + 3)(x + 2) = 0 Thus 2x + 3 = 0 => x = -1.5 or x + 2 = 0 => x = -2

2x2 + 2y - 8 = 0 2(x2 + y - 4) = 0 and other than removing the two outside the bracket, this cannot be factorised further, nor simplified.

(x - 4)(2x + 3)

use algebra and then factor... x= -9 and 9

2x2 - 8x + 3 = 0 needs to be solved using the quadratic formula.x = (4 + sqrt(10))/2 or x = (4 - sqrt(10))/2

The curve turns at a minimum: (2.5, -12)